Ground and satellite observations of low‐latitude red auroras at the initial phase of magnetic storms. Issue 1 (31st January 2013) - Shiokawa, K.; Miyoshi, Y.; Brandt, P. C.; Evans, D. S.; Frey, H. U.; Goldstein, J.; Yumoto, K.
Abstract : [1] We report ground and satellite observations of unique low‐latitude red auroras that appear at the initial phase of geomagnetic storms. For two events on 21 October 2001, and 6 April 2000, the low‐latitude red auroras appeared at 45° MLAT ( L ∼ 2) ∼ 1.5 h after the storm sudden commencement in the postmidnight sector in Japan. Comprehensive satellite data were available for the former event. The energetic neutral atom images obtained by the Imager for Magnetopause‐to‐Aurora Global Exploration satellite show rapid enhancement of ring current hydrogen and oxygen fluxes at radial distances of ∼ 2–8 RE after the storm sudden commencement and associated with several storm‐time substorms. The hydrogen ring‐current enhancement occurred particularly in the postmidnight sector where the red aurora was observed. The timing of oxygen flux enhancement associated with a storm‐time substorm coincided with the red aurora appearance. This rapid and significant enhancement of energetic neutral atom flux was also confirmed by energetic ion data obtained by the NOAA/POES‐16 satellite. Extreme ultraviolet plasmaspheric images obtained by Magnetopause‐to‐Aurora Global Exploration indicate that the plasmapause was located at L = 2.3–2.5 in the postmidnight sector during the event, indicating that a spatial overlap occurs between the plasmasphere and the enhanced ring current ions at L ∼ 2. Based on these observations, we suggest that large energization of high‐energy ring‐current ions in the postmidnight inner magnetosphere caused the spatial overlap of these ring‐current ions with the low‐energy plasmaspheric plasmas at L ∼ 2, producing the low‐latitude red auroras at the very beginning of the storms. Key Points: First comprehensive satellite observation during low‐latitude red aurora Low‐latitude red auroras appear at the very beginning of geomagnetic storm Satellite image data suggest overlap of ring current and plasmasphere